Transoral incisionless fundoplication as rescue therapy for gastroesophageal reflux in a lung transplant recipient - William King, MD; Hannah Zuercher, MD; Manuel Amaris, MD; Amir Emtiazjoo, MD; Mindaugas Rackauskas, MD, PhD; Bashar Qumseya, MD, MPH (VideoGIE)
Background and Aims: A patient with a prior lung transplant and surgical fundoplication had severe recurrent gastroesophageal reflux disease (GERD) and chronic retrograde microaspiration, which both threatened his graft function and elevated his risk for retransplant. He was deemed a poor candidate for surgical fundoplication. We therefore aimed to perform a transoral incisionless fundoplication (TIF). Methods: The gastroesophageal flap valve was loose on diagnostic esophagogastroduodenoscopy. We used a plication device to repair the existing fundoplication, forming a 270°, 3-cm wrap using 12 H-type fasteners. Results: Erosive esophagitis improved from Los Angeles grade C to A and acid exposure time from 30% to 5%. Heartburn symptoms resolved. He underwent repeat lung transplant. Conclusions: The video in this case demonstrates the technique for TIF after surgical fundoplication. This case also supports the use of TIF as rescue therapy for post-lung transplant GERD.